Content and quality of workplace guidelines developed to prevent mental health problems: results from a systematic review - Nexø, Mette A; Kristensen, Josefine Vejlby; Grønvad, Majbritt Thorhauge; Kristiansen, Jesper; Poulsen, Otto Melchior (Scandinavian Journal of Work, Environment & Health, 2018)
' ' OBJECTIVES ': 'A wide range of guidelines have been developed to prevent work-related mental health problems (MHP), but little is known about the quality of such guidelines. We systematically reviewed the content and quality of workplace guidelines aiming to prevent, detect, and/or manage work-related MHP. ' ' METHODS ': 'We conducted systematic online and database searches (MEDLINE; Web of Science; PsychNET; occupational safety and health databases) to identify guidelines. Eligibility criteria included guidelines recommending primary, secondary, or tertiary preventive interventions to be implemented at the workplace by employers, employees or organizational staff. A minimum of minimum three independent reviewers assessed the quality of guidelines using the Guidelines for Research and Evaluation (AGREE II). Guidelines rated ≥65% with regards to domain I, II, and III were considered to be of good developmental quality. ' ' RESULTS ': 'Seventeen guidelines were quality assessed. Guidelines mainly targeted employers: eight guidelines recommended primary preventive interventions (eg, reduction of psychosocial hazards by risk management procedures), three recommended tertiary (eg, stay at work or return to work procedures for management), and six recommended a combination of primary, secondary and tertiary interventions (eg, facilitate return to work by increasing mental health literacy of all staff and coordination of sick-listed employees). Four guidelines had developed recommendations of good quality, but the evidence of two guidelines was outdated and studies documenting the effect of implementation were not yet available. ' ' CONCLUSIONS ': 'Few guidelines have been developed with sufficient rigor to help employers prevent or manage work-related MHP and evidence of their effectiveness remains scarce.
Keywords: depression; mental health problem; review; sick-leave; systematic review; work disability; workplace guideline; workplace intervention